INFLUENCE OF ROLLING STOCK VIBROACOUSTICAL PARAMETERS ON THE CHOICE OF RATIONAL VALUES OF LOCOMOTIVE RUNNING GEAR - Zelenko, Yu. V.; Neduzha, L. O.; Shvets, A. O. (Science and Transport Progress, 2021)
Purpose.The success of the traffic on the railways of Ukraine depends on the number and the operational fleet of electric locomotives. Today, the locomotive depot exploit physically and morally outdated locomotives that have low reliability. Modernization of electric locomotives is not economically justified. The aim of this study is to improve the safety of the traction rolling stock by the frequency analysis of dynamical systems, which allows conducting the calculation of the natural (of resonant) frequencies of the design and related forms of vibrations.Methodology.The study was conducted by methods of analytical mechanics and mathematical modeling of operating loads of freight locomotive when driving at different speeds on the straight and curved track sections. The theoretical value of the work is the technique of choice of constructive schemes and rational parameters of perspective electric locomotive taking into account the electric inertia ratios and stiffness coefficients of Lagrange second-order equations.Findings. The problems of theoretical research and the development of a mathematical model of the spatial electric vibrations are solved. The theoretical studies of the effect of inertia ratios and stiffness coefficients on the dynamic values and the parameter values of electric locomotive undercarriages are presented.Originality.The set of developed regulations and obtained results is a practical solution to selecting rational parameters of bogies of the freight mainline locomotive for railways of Ukraine. A concept of choice of constructive scheme and rational parameters of perspective locomotive is formulated. It is developed the method of calculation of spatial electric locomotive oscillations to determine its dynamic performance. The software complex for processing the data of experimental studies of dynamic parameters of electric locomotive and comparing the results of the theoretical calculations with the data of full-scale tests is implemented.Practicalvalue.The theoretical study allows objectively assessing the impact of the partial frequency of electric locomotive elements on both the rational parameters of its underframe, and the performance and physiological condition of the locomotive crew. Thus, the practical value of the whole complex of theoretical research was to develop an algorithm and program, choosing rational parameters and design scheme of electric locomotive running gear. Using a software package for the study of spatial fluctuations of electric locomotive made it possible to evaluate the dynamic performance of the electric locomotive underframe with sufficient accuracy for practical problems.